Biomimetic Metal–Organic Framework Nanoparticles for Cooperative Combination of Antiangiogenesis and Photodynamic Therapy for Enhanced Efficacy. Issue 15 (18th February 2019) - Min, Huan; Wang, Jing; Qi, Yingqiu; Zhang, Yinlong; Han, Xuexiang; Xu, Ying; Xu, Junchao; Li, Yao; Chen, Long; Cheng, Keman; Liu, Guangna; Yang, Na; et al.
Abstract: Photodynamic therapy (PDT) is a promising anticancer treatment and is clinically approved for different types of tumors. However, current PDT suffers several obstacles, including its neutralization by excess glutathione (GSH) in the tumor tissue and its strongly proangiogenic tumor response. In this work, a biomimic, multifunctional nanoparticle‐based PDT agent, combining a tumor‐targeted photosensitizer with GSH scavenging and antiangiogenesis therapy, is developed. A porphyrinic Zr–metal–organic framework nanoparticle is used simultaneously as the photosensitizer and the delivery vehicle of vascular endothelial growth factor receptor 2 (VEGFR2) inhibitor apatinib. The core nanoparticles are wrapped in MnO2 to consume the intratumoral GSH and then decorated with a tumor cell membrane camouflage. After intravenous administration, the nanoparticles selectively accumulate in tumor through homotypic targeting mediated by the biomimic decoration, and the combination of enhanced PDT and antiangiogenic drug significantly improves their tumor inhibition efficiency. This study provides an integrated solution for mechanism‐based enhancement of PDT and demonstrates the encouraging potential for multifunctional nanosystem applicable for tumor therapy. Abstract : A multifunctional biomimetic metal–organic framework (MOF) nanoplatform (aMMTm) is constructed to simultaneously overcome multiple obstacles in photodynamic therapy through combination with antiangiogenesis and GSH scavenging. This versatile nanoplatform also enables homotypic tumor targeting and improved MOF plasma pharmacokinetics, offering a promising strategy for enhanced photodynamic therapy.